Effect of water pressure inside inflatable rock bolts on their anchoring capacity - Giraldo Paredez, Emiliano Mauro (2013)
n a previous study undertaken in march 2011 at Reliquias mine owned by Cía. Minera Castrovirreyna, it was demonstrated that hydrabolts in underground rock support, can bear greater load capacity than any of the three other rock bolts tested (Swellex, threaded rebar and split set). Thisadvantage of the hydrabolt motivated us to continue analyzing reasons for this and other variables. This study included compression tests on 18 high pressure water loaded hydrabolts, 18 water unloaded hydrabolts and one swellex. These tests were carried out at the material laboratory of the Pontificia Universidad Católica del Perú (PUCP). Maximum load on water loaded hydrabolt was 400KN, on the unloaded 50 KN and on the swellex bolts 59 KN. By analyzing the information gathered on these tests and in the previous trials, it is shown that limit elastic loads for hydrabolts are: 120 KN for water loaded, 36.8 for non loaded and 30 KN for swellex bolt. It is also concluded from the diametric deformation under load and non load that hydra bolts loaded are 375 % higher in load capacity than the unloaded and swellex bolts. Analyzing the differential deformation due to peak applied load, the un loaded hydrabolts recovers an average of only 5.4 millimeters of its original length and the loaded hydrabolt 12 millimeter.